Spiritual Leadership in Healthcare: A Bibliometric Analysis - Dienda Sesioria Assyakur; Elsye Maria Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Spiritual leadership is one of the leadership styles that are currently popular in management studies. It has vision, hope, faith, and altruistic love to create a positive environment in an organization. Goals. Provide information through bibliometric analysis of publishing patterns, literature developments, and information analysis of spiritual leadership research publications. This study included quantitative descriptive approaches and bibliometric analyses to map bibliographic data from various journal articles from the Scopus database using VOSviewer. This study retrieves data on December 15, 2021, using the keywords "spiritual AND leadership" OR "Islamic AND leadership". United States, United Kingdom, and Indonesia contributed the most to the study. Frontiers in Psychology journal has published the most papers on spiritual leadership. The topic areas with the most documents are social science, medicine, arts, and humanities, as well as business, management, and accounting. Vosviewer categorizes data into four clusters. Cluster 1 includes themes such as health, care, quality, and evidence. Cluster 2 covers spiritual leadership, relationships, Indonesia, influence, the environment, employee commitment, and organizational commitment. Cluster 3 includes the issues of assistance, reaction, spiritual leadership, and contribution. The last, cluster 4 covers religion, Islam, power, and important role.  Abstrak: Kepemimpinan spiritual merupakan gaya kepemimpinan yang saat ini populer dalam studi manajemen. Terdapat visi, harapan, keyakinan, dan cinta altruistik untuk menciptakan lingkungan yang positif dalam sebuah organisasi. Tujuan. Memberikan informasi melalui analisis bibliometrik tren publikasi, perkembangan literatur, dan analisis informasi publikasi dari penelitian kepemimpinan spiritual. Penelitian ini mencakup pendekatan deskriptif kuantitatif dan analisis bibliometrik untuk memetakan data bibliografi dari berbagai artikel jurnal dari database Scopus menggunakan VOSviewer. Penelitian ini mengambil data pada tanggal 15 Desember 2021 dengan menggunakan kata kunci “spiritual AND leadership” ATAU “Islamic AND leadership”. Amerika Serikat, Inggris, dan Indonesia berkontribusi paling besar dalam penelitian ini. Jurnal Frontiers in Psychology telah menerbitkan makalah paling banyak tentang kepemimpinan spiritual. Bidang topik dengan dokumen terbanyak adalah ilmu sosial, kedokteran, seni, dan humaniora, serta bisnis, manajemen, dan akuntansi. Vosviewer mengkategorikan data menjadi empat cluster. Klaster 1 mencakup tema-tema seperti kesehatan, perawatan, kualitas, dan bukti. Klaster 2 meliputi kepemimpinan spiritual, hubungan, Indonesia, pengaruh, lingkungan, komitmen karyawan, dan komitmen organisasi. Klaster 3 meliputi masalah bantuan, reaksi, pemimpin spiritual, dan kontribusi. Terakhir, cluster 4 meliputi agama, Islam, kekuasaan, dan peran penting.